A DESCRIPTIVE STUDY ON ENGLISH LEARNING MOTIVATION OF TENTH YEAR STUDENTS IN THE MIDST OF COVID-19 - Hujaini; Tri Mulyati; Abdul Halim (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2022)
This research is a descriptive study of students motivation using descriptive quantative approach. This research aimed to know the student motivation in learning English on the tenth year student In the Midst of Covid-19 at MAU (Featured Islamic School) Ihya’ Ulumiddin Singojuruh academic year 2020-2021. The researcher used questionnaire to collect the data. The indicators of the questionnaire were divided into two part; indicators of integrative and instrumental motivations. The researcher used the Likert scale with four alternative answers, those are strongly agree, agree, disagree and strongly disagree. The researcher analyzed the data of questionnaires by formula : P = n/N x 100%. The research results that the students’ integrative motivation in learning English is categorized as very high motivation and the students’ instrumental motivation is categorized as very high motivation.